2018
DOI: 10.2147/cmar.s158013
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of RRBP1 in esophageal carcinoma

Abstract: ObjectiveThis study was to investigate the expression and clinical significance of RRBP1 in esophageal carcinoma.Materials and methodsRRBP1 expression was detected in 120 esophageal carcinoma and matched adjacent normal tissues, and the relationship of RRBP1 with clinicopathological characteristics and prognosis was analyzed.ResultsRRBP1 was highly expressed in esophageal carcinoma tissues compared with matched adjacent normal tissues (P<0.05). Moreover, RRBP1 expression was associated with T stage, lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
(29 reference statements)
4
23
0
Order By: Relevance
“…Compared with patients with low RRBP1 expression, patients with high RRBP1 expression had shorter disease-specific survival. RRBP1 was also highly expressed in esophageal carcinoma tissues and was associated with T stage, lymph node metastasis, TNM stage and survival (8). Similar studies were performed in endometrial endometrioid adenocarcinoma and prostate cancer, and RRBP1 was recognized as a potential protein marker (6,7).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Compared with patients with low RRBP1 expression, patients with high RRBP1 expression had shorter disease-specific survival. RRBP1 was also highly expressed in esophageal carcinoma tissues and was associated with T stage, lymph node metastasis, TNM stage and survival (8). Similar studies were performed in endometrial endometrioid adenocarcinoma and prostate cancer, and RRBP1 was recognized as a potential protein marker (6,7).…”
Section: Discussionsupporting
confidence: 59%
“…RRBP1 inhibition could cause ER stress and significantly reduce cell tumorigenicity (4) RRBP1 was reported to be overexpressed in lung, colorectal, endometrial and prostate cancer (4)(5)(6)(7). High RRBP1 expression could promote esophageal and colorectal cancer progression, and can be used to predict patient prognosis (5,8). However, to the best of our knowledge, the expression of RRBP1 in bladder cancer has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…RRBP1 is localized in the rough endoplasmic reticulum (rER) and supposed to play a role in secretion of newly synthesized protein [19]. RRBP1 is reported to be over expressed in breast [20], lung [19], colorectal [21], esophageal [22], endometrial [23], prostate [24] and ovarian cancer [25] patient tissues. RRBP1 expression is associated with the disease progression and also envisaged as an unfavourable post-operative prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…(10) In addition, we also found that RRBP1 is overexpressed in a variety of tumor cells, including liver cancer, prostate cancer, colorectal cancer, lung cancer, Her-2 (+) breast cancer, esophageal cancer, endometrial cancer and ovarian cancer. (10)(11)(12)(13)(14)(15)(16)(17) However, to date, few has explored the relationship between RRBP1 overexpression and the prognosis of cervical squamous cell carcinoma. The purpose of the present study was to investigate whether RRBP1 was overexpressed in cervical squamous cell carcinoma through immunohistochemistry, Western blotting and qRT-PCR.…”
Section: Introductionmentioning
confidence: 99%
“…According to a large number of previous studies, it was found that RRBP1 may interact with kinesin family member 5B (KIF5B) to participate in the accumulation of autophagosomes in tumor cells, and overexpression of RRBP1 causes ER stress to be alleviated and stabilized, leads to the accumulation of unfolded and folded proteins (UPR) in the endoplasmic reticulum, resulting in abnormal protein function, which can lead to cancer (18). Recently, overexpression of rrbp1 was found in liver cancer, prostate cancer, colorectal cancer, lung cancer, Her-2 (+) breast cancer, esophageal cancer, in endometrial cancer and in ovarian cancer and was closely associated with poor prognosis (9,10,(12)(13)(14)(15)(16)(17). …”
mentioning
confidence: 99%